THE ROLE OF TRAINING AND DEVELOPMENT, WORK ENVIRONMENT AND JOB SATISFACTION IN STAFF RETENTION; MODERATING ROLE OF TRANSFORMATIONAL LEADERSHIP - Sultan Saleem; Anwar Shamim; Sher Ali Khan; Kifayat Ullah (International Journal of Contemporary Issues in Social Sciences, 2023)
Employee retention is a critical concern for organizations in today’s dynamic and competitive business landscape. This research examines the multifaceted factors contributing to staff retention, with a specific focus on the roles of training and development, work environment, and job satisfaction, while considering the moderating influence of transformational leadership. This study addresses the gap in knowledge by examining the effects of job satisfaction, working environment, and training & development on staff retention through the moderating influence of transformational leadership. A quantitative research methodology was used to a pre-tested instrument. For this study, multi-source data was provided by the 340 employees of private banking sectors in Islamabad and Rawalpindi. Based to the study findings, the research study found that TD, WE, JS has a positive and significant impact on staff retention. Therefore, the transformational leadership moderates the positive relationship between TD, WE, and JS on staff retention. The conclusions have an extensive range of implications for academics and professionals, especially for the private banking sectors. The study’s limitations are also examined, along with the potential and practical implications they provide.